Control interno y calidad de la información financiera en el Hospital Regional de Pucallpa 2024 - Guerra Missly, Nataly Isabel (2024)
The purpose of this report is to determine the relationship between internal control and quality of financial information at the Regional Hospital of Pucallpa 2024, this research was basic, correlational descriptive level with a non experimental design, choosing 30 workers as a sample. to whom the questionnaire was applied as a data collection instrument. According to the results obtained, it is shown that the level of internal control is regular (30%), because the control environment dimension, management control activities, information and communication, as well as supervision are evaluated as regular, while that the risk assessment is considered adequate. For its part, the level of quality of financial information is high (34%) since understandability, reliability and comparability are the most notable aspects in this evaluation, while relevance is considered at a regular level. Consequently, it has been determined that there is a significant and positive relationship between internal control and the quality of financial information, corroborated by a correlation coefficient of 0.640 and a significance level of 0.000.